The Green Economy and the Water-Energy-Food Nexus - Brears, Robert C. (Palgrave Macmillan UK, 2018)
This book argues that a variety of policies will be required to create synergies between the water-energy-food nexus sectors while reducing trade-offs in the development of a green economy. Despite rising demand for water, energy and food globally, the governance of water-energy-food sectors has generally remained separate with limited attention placed on the interactions that exist between them. Brears provides readers with a series of in-depth case studies of leading cities, states, nations and regions of differing climates, lifestyles and income-levels from around the world that have implemented a variety of policy innovations to reduce water-energy-food nexus pressures and achieve green growth. The Green Economy and the Water-Energy-Food Nexus will be of interest to town and regional planners, resource conservation managers, policymakers, international companies and organisations interested in reducing water-energy-food nexus pressures, environmental NGOs, researchers, graduate and undergraduate students.